Preparation method and application of graphene aerogel with multiple pores

CN119430168BActive Publication Date: 2026-10-30CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411821074.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2026-10-30
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

该方法可通过控制冷冻温度及速度精确控制孔径大小,然而该方法制备的石墨烯气凝胶孔道结构单一,孔壁厚,孔隙率较低,单位质量的材料孔道丰富度不足

Benefits of technology

[0024](1)本发明所述的石墨烯气凝胶的制备方法简单,成本低廉,可实现大规模制备,有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430168B_ABST
    Figure CN119430168B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of graphene aerogel with multiple pores, and belongs to the technical field of heat insulation and adsorption materials. The preparation method comprises the following steps: mixing an oxidized graphene water dispersion liquid and an oil phase according to a set volume ratio, and performing high-speed shearing to obtain an oil-in-water emulsion; performing step-by-step one-way freezing on the oil-in-water emulsion, and obtaining an oxidized graphene solid hydrogel through step-by-step water-oil solidification; performing vacuum drying on the oxidized graphene solid hydrogel, and obtaining an oxidized graphene aerogel with multiple pores; and performing high-temperature reduction on the oxidized graphene aerogel, and obtaining a graphene aerogel with multiple pores. The pore structure of the graphene aerogel prepared by the application is significantly different in different directions, so that the material can be applied to different fields such as heat insulation, photo-thermal oil absorption and catalyst carrier, the preparation process is simple, the cost is low, the material can be prepared on a large scale, and the graphene aerogel has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal insulation and adsorption materials, and in particular to a method for preparing a graphene aerogel with multiple pores for use in thermal insulation and oil spill treatment. Background Technology

[0002] With global economic development and population growth, the demand for energy is constantly increasing across various sectors, including industrial production, urbanization, transportation, agriculture, and daily life. Traditional energy resources such as coal, oil, and natural gas are finite resources with limited reserves and are non-renewable. As these traditional energy resources are exploited and consumed, their supply is gradually decreasing and becoming increasingly difficult to obtain. Energy supply is affected by various factors, including natural disasters and man-made accidents, leading to energy supply interruptions or instability, further exacerbating the energy shortage problem. This is why we need to advocate for energy conservation and recycling. Energy depletion is a real problem, and taking proactive measures such as developing renewable energy, improving energy efficiency, promoting energy-saving technologies, and strengthening energy management are imperative to address the challenges of the energy crisis.

[0003] Thermal insulation materials and adsorbent materials play crucial roles in energy conservation and recovery. Thermal insulation materials are irreplaceable in energy conservation and are widely used in buildings, industrial equipment, and pipelines. They reduce heat exchange between the inside and outside of buildings and installations, slow down heat transfer rates, reduce heat loss, lower the load on heating systems, and improve energy efficiency, thereby saving energy and reducing energy costs. Furthermore, the extraction, transportation, and utilization of oil resources have led to frequent oil spills, posing a significant threat to the ecological environment, wasting vast amounts of energy, and causing substantial social and economic losses. Adsorbent materials are of great importance for the recovery of leaked oil. For example, in offshore oil spills, as light components evaporate and heavy components remain, the viscosity of the crude oil increases significantly, reducing its fluidity and making it extremely difficult to handle. However, crude oil viscosity decreases significantly with increasing temperature; therefore, developing an adsorbent material that can reduce the viscosity of leaked crude oil by heating it is a feasible approach.

[0004] Graphene is a type of graphene formed by the sp(s) of carbon atoms. 2Two-dimensional sheet carbon materials with a honeycomb lattice structure, formed by hybrid interconnections, possess stable chemical properties and good thermal conductivity. Aerogels are porous materials with low thermal conductivity and high specific surface area. Graphene aerogels combine most of the advantages of graphene and aerogels and are widely used in thermal insulation and adsorption fields. For example, Chen Lijun et al. prepared graphene aerogel fibers (graphene aerogel fibers, graphene aerogel insulation flakes and their preparation methods, CN114717688A) by wet spinning, reduction, and supercritical carbon dioxide drying of graphene oxide liquid crystal. This material has the advantages of high gas thermal conductivity suppression efficiency and low thermal conductivity, and has good thermal insulation performance. However, the small pore size of this material limits its application in the adsorbent field. Zhang Hailong et al. (A method for preparing graphene aerogel with adjustable pore size, CN109133040A) used ice crystals as templates to prepare graphene aerogels with precisely controllable pore size by reducing and freezing a suspension of graphene oxide. This method allows for precise control of pore size by adjusting the freezing temperature and rate; however, the graphene aerogels prepared by this method have a simple pore structure, thick pore walls, low porosity, and insufficient pore abundance per unit mass of material.

[0005] Therefore, developing graphene aerogels with unique pore structures and simple preparation processes is of great significance for achieving large-scale energy conservation and resource recycling. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing and applying graphene aerogels with multiple pores, thus resolving the problems mentioned above. This invention prepares a graphene aerogel with multiple pores by stepwise unidirectional freezing of an unstable oil-in-water emulsion, followed by vacuum drying and high-temperature reduction. The prepared material exhibits extremely high porosity and anisotropic thermal conductivity, making it suitable for both energy conservation in thermal insulation and rapid recovery of crude oil and efficient energy utilization in photothermal adsorption.

[0007] The present invention adopts the following technical solution.

[0008] The first aspect of this invention discloses a method for preparing graphene aerogel with multiple channels, comprising the following steps:

[0009] An unstable oil-in-water emulsion was obtained by mixing an aqueous dispersion of graphene oxide with an oil phase at a set volume ratio and then performing high-speed shearing.

[0010] The obtained oil-in-water emulsion was subjected to stepwise unidirectional freezing, and graphene oxide solid hydrogel was obtained through stepwise solidification of water and oil.

[0011] The obtained graphene oxide solid hydrogel was vacuum dried to remove oil and water from the inside and surface of the pores, thus obtaining graphene oxide aerogel with multiple pores.

[0012] The obtained graphene oxide aerogel was reduced at high temperature to obtain a graphene aerogel with multiple pores.

[0013] Preferably, the oil phase component is a substance that is incompatible with water and has different freezing points under the same pressure, and the set volume ratio of the oil phase to the water phase is 1:1 to 1:5.

[0014] Preferably, the high-speed shearing rotation speed is not less than 10,000 r / min, and the time is 1 to 5 min.

[0015] Preferably, the step-by-step cooling unidirectional freezing specifically includes: placing the obtained oil-in-water emulsion in a mold, so that its bottom surface contacts an ultra-low temperature cold source, and performing unidirectional freezing.

[0016] Preferably, the mold is wrapped with heat-insulating material around the top and sides of the container containing the aerogel, leaving only the bottom of the container unwrapped, so that its bottom surface is in contact with the ultra-low temperature cold source.

[0017] Preferably, the ultra-low temperature cold source is any one of a refrigerant or a refrigeration device.

[0018] Preferably, during the unidirectional freezing process, the mold containing the oil-in-water emulsion is placed at a temperature below the solidification point of one phase and above the solidification point of the other phase for a set time, and then placed at a temperature below the solidification point of the other phase for a set time.

[0019] Preferably, the vacuum drying pressure is 10 Pa or less, and the time is 12 hours or more;

[0020] The high-temperature reduction temperature is 200–700℃.

[0021] The second aspect of the present invention discloses an application of the graphene aerogel prepared by the preparation method, wherein the graphene aerogel with multiple channels is applied to a thermal insulation method, wherein the internal channels of the graphene aerogel material are attached parallel to the surface of the object requiring thermal insulation to block heat transfer.

[0022] The third aspect of the present invention discloses an application of the graphene aerogel prepared by the preparation method. The graphene aerogel with multiple channels is applied to a photothermal oil absorption method. Under sunlight, the internal channels of the graphene aerogel material are placed on the oil surface perpendicular to the oil surface. After the material absorbs light, it heats up and heats the oil, thereby reducing the viscosity of the oil and achieving adsorption.

[0023] Compared with the prior art, the beneficial effects of the present invention include at least the following:

[0024] (1) The preparation method of the graphene aerogel described in this invention is simple, low in cost, and can be prepared on a large scale, with broad application prospects.

[0025] (2) The preparation method adopted in this invention is to shape the material into isotropic primary channels by unstable GO-O / W emulsion droplets; then, one phase is solidified by step-cooling unidirectional freezing, and then another phase is solidified, thereby stabilizing the primary channels and promoting the directional arrangement of the primary channels to form the final multi-channel structure. Step-cooling unidirectional freezing can make the multi-channel graphene aerogel have an anisotropic structure. By simply adjusting the freezing temperature and the volume ratio of the oil phase to the water phase, materials with different properties can be prepared.

[0026] (3) The graphene aerogel with multiple channels described in this invention has high porosity, anisotropic thermal conductivity, good thermal insulation performance perpendicular to the channel arrangement direction, good heat transfer performance parallel to the channel arrangement direction, high adsorption rate and large adsorption amount for crude oil, and can be used as both thermal insulation material and adsorption material at the same time. It can be widely used in energy conservation, environmental protection and other fields. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the material preparation method of the present invention;

[0028] Figure 2 SEM image of the graphene aerogel with multiple channels obtained in Example 5;

[0029] Figure 3 The graphene aerogel with multiple channels obtained in Example 5 was subjected to a pressure of 1000 W / m 2 The curve showing the change in the mass of high-viscosity oil adsorbed along the ice crystal growth direction over time during a photothermal-oil absorption experiment under intense light irradiation;

[0030] Figure 4 The graphene aerogel with multiple channels obtained in Example 5 was subjected to a pressure of 1000 W / m 2 The temperature change curves of the upper and lower surfaces over time when high viscosity oil is adsorbed along the ice crystal growth direction during photothermal-oil absorption experiments under intense light irradiation;

[0031] Figure 5 This is a SEM image of the graphene aerogel with multiple channels obtained in Example 7. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of this invention. The embodiments described in this application are merely some embodiments of this invention, and not all embodiments. Based on the spirit of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of this invention.

[0033] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing graphene aerogel with multiple channels, comprising the following steps:

[0034] Step 1: Mix the graphene oxide aqueous dispersion with the oil phase at a set volume ratio, and then perform high-speed shearing to obtain an unstable oil-in-water (GO-O / W) emulsion.

[0035] In a preferred but non-limiting embodiment of the present invention, in step 1, the amount of graphene oxide in the graphene oxide aqueous dispersion is 0.1 to 1 part graphene oxide per 100 parts of water, and the content of graphene oxide may be higher.

[0036] The oil phase components can be selected from alkanes, alkenes, benzene and its homologues, halogenated hydrocarbons, oils, esters, higher alcohols, petroleum, and other substances that are incompatible with water and have different freezing points under the same conditions.

[0037] The volume ratio of the oil phase to the water phase is 1:1 to 1:5, and more preferably, the volume ratio of the oil phase to the water phase is 1:1.25 to 1:2.5.

[0038] The high-speed shearing speed is 10,000 r / min or higher, and the time is 1 to 5 min.

[0039] Step 2: The GO-O / W emulsion obtained in Step 1 is subjected to stepwise unidirectional freezing, and graphene oxide solid hydrogel is obtained by stepwise solidification of water and oil.

[0040] In step 2, the specific steps of the step-by-step cooling unidirectional freezing are as follows: the GO-O / W emulsion obtained in step 1 is placed in a mold, and its bottom surface is brought into contact with an ultra-low temperature cold source for unidirectional freezing.

[0041] The mold is made by wrapping the top and sides of the aerogel container with heat insulation material, leaving only the bottom of the container unwrapped, so that the bottom can come into contact with the ultra-low temperature cold source.

[0042] The ultra-low temperature cold source is a refrigerant such as liquid carbon dioxide, liquid ammonia, or liquid nitrogen, or a refrigeration device such as an ultra-low temperature freezer.

[0043] In the step-down unidirectional freezing process, the sample is frozen at a temperature below the solidification point of one phase and above the solidification point of the other phase for a period of time, and then frozen at a temperature below the solidification point of the other phase for a period of time.

[0044] It is worth noting that in this embodiment, "one phase" and "the other phase" refer to the oil phase and water phase mentioned in step 1. However, this is not the case in all experiments. The freezing order of the two phases is not fixed and depends on the freezing points of the water and oil phases. When the freezing point of the selected organic material is higher than that of water, the cooling process will show that the oil phase freezes first and then the water phase freezes. When the freezing point of the organic material is lower than that of water, the order is reversed. Therefore, the specific phases are not limited here, but "one phase" and "the other phase" are used instead.

[0045] For example, when the oil phase component is selected as cyclohexane, the sample is frozen for a period of time at a temperature below the freezing point of cyclohexane and above the freezing point of water (1°C), and then the sample is frozen for a period of time at a temperature below the freezing point of water (-25 to -65°C).

[0046] Step 3: Vacuum dry the graphene oxide solid hydrogel obtained in Step 2 to remove oil and water from the inside and surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0047] In step 3, the vacuum drying pressure is 10 Pa or less, and the time is 12 hours or more.

[0048] Step 4: The graphene oxide aerogel obtained in Step 3 is subjected to high-temperature reduction to obtain a graphene aerogel with multiple channels.

[0049] In step 4, the high-temperature reduction is carried out in a tube furnace at a temperature of 200–700°C.

[0050] Materials with different properties can be prepared by simply adjusting the freezing temperature and the volume ratio of the oil phase to the water phase. Specifically, decreasing the freezing temperature increases the thermal conductivity of the material along the ice crystal growth direction and decreases the thermal conductivity perpendicular to the ice crystal growth direction, thus reducing the adsorption rate of crude oil. Increasing the volume ratio of the oil phase to the water phase increases the thermal conductivity of the material along the ice crystal growth direction, thus increasing the adsorption capacity of crude oil.

[0051] The principle upon which this invention is based is: using unstable GO-O / W emulsion droplets to shape isotropic primary channels in the material; then using stepwise cooling unidirectional freezing to first solidify one phase and then solidify the other phase, thereby stabilizing the primary channels and promoting the directional alignment of the primary channels to form the final multi-channel structure.

[0052] Another embodiment of the present invention provides an application of graphene aerogel with multiple channels. The graphene aerogel with multiple channels obtained based on the preparation method is used for thermal insulation and photothermal oil absorption, specifically:

[0053] The heat insulation method involves attaching the internal pores of graphene aerogel material parallel to the surface of the object requiring heat insulation, thereby blocking heat transfer.

[0054] The aforementioned photothermal oil absorption method involves placing a graphene aerogel material with its internal pores perpendicular to the oil surface under sunlight. After absorbing light, the material rapidly heats up and heats the oil, reducing its viscosity and achieving rapid adsorption. At the same time, it effectively prevents heat loss from all sides, improving energy utilization efficiency.

[0055] Example 1:

[0056] (1) Formulation of GO-O / W emulsion

[0057] Cyclohexane and graphene oxide aqueous dispersion were mixed at a volume ratio of 1:2.5 and subjected to high-speed shearing to prepare an unstable GO-O / W emulsion.

[0058] (2) Preparation of graphene oxide solid hydrogel

[0059] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 hour to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 hour to obtain graphene solid hydrogel.

[0060] (3) Preparation of graphene oxide aerogel

[0061] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water from the inside and surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0062] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400°C for 2 hours to obtain a graphene aerogel with multiple channels.

[0063] (5) Thermal conductivity measurement

[0064] The thermal conductivity of the graphene aerogel with multiple channels prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.087 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.063 W / (m·K).

[0065] (6) Photothermal adsorption of crude oil

[0066] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. When the adsorption reached saturation, each gram of aerogel could adsorb 233.25 times its own mass of high-viscosity crude oil, and the adsorption rate was 11.66 g / (g·min).

[0067] Example 2:

[0068] (1) Formulation of GO-O / W emulsion

[0069] Cyclohexane and graphene oxide aqueous dispersion were mixed at a volume ratio of 1:2.5 and subjected to high-speed shearing to prepare an unstable GO-O / W emulsion.

[0070] (2) Preparation of graphene oxide solid hydrogel

[0071] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 hour to solidify the cyclohexane droplets inside, and then placed on a cold source at -45°C for unidirectional freezing for 1 hour to obtain graphene solid hydrogel.

[0072] (3) Preparation of graphene oxide aerogel

[0073] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water inside and on the surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0074] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400°C for 2 hours to obtain a graphene aerogel with multiple channels.

[0075] (5) Thermal conductivity measurement

[0076] The thermal conductivity of the graphene aerogel with multiple channels prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.092 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.059 W / (m·K).

[0077] (6) Photothermal adsorption of crude oil

[0078] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. When the adsorption reached saturation, each gram of aerogel could adsorb 240.37 times its own mass of high-viscosity crude oil, and the adsorption rate was 10.93 g / (g·min).

[0079] Example 3:

[0080] (1) Formulation of GO-O / W emulsion

[0081] Cyclohexane and graphene oxide aqueous dispersion were mixed at a volume ratio of 1:2.5 and then subjected to high-speed shearing to prepare an unstable GO-O / W emulsion.

[0082] (2) Preparation of graphene oxide solid hydrogel

[0083] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 hour to solidify the cyclohexane droplets inside, and then placed on a cold source at -65°C for unidirectional freezing for 1 hour to obtain graphene solid hydrogel.

[0084] (3) Preparation of graphene oxide aerogel

[0085] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water inside and on the surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0086] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400°C for 2 hours to obtain a graphene aerogel with multiple channels.

[0087] (5) Thermal conductivity measurement

[0088] The thermal conductivity of the graphene aerogel with multiple channels prepared by (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.106 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.052 W / (m·K).

[0089] (6) Photothermal adsorption of crude oil

[0090] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. When the adsorption reached saturation, each gram of aerogel could adsorb 226.54 times its own mass of high-viscosity crude oil, and the adsorption rate was 9.85 g / (g·min).

[0091] Example 4:

[0092] (1) Formulation of GO-O / W emulsion

[0093] Cyclohexane and graphene oxide aqueous dispersion were mixed at a volume ratio of 1:1.67 and subjected to high-speed shearing to prepare an unstable GO-O / W emulsion.

[0094] (2) Preparation of graphene oxide solid hydrogel

[0095] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 hour to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 hour to obtain graphene solid hydrogel.

[0096] (3) Preparation of graphene oxide aerogel

[0097] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water inside and on the surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0098] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400°C for 2 hours to obtain a graphene aerogel with multiple channels.

[0099] (5) Thermal conductivity measurement

[0100] The thermal conductivity of the graphene aerogel with multiple channels prepared by (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.094 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.061 W / (m·K).

[0101] (6) Photothermal adsorption of crude oil

[0102] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. When the adsorption reached saturation, each gram of aerogel could adsorb 238.24 times its own mass of high-viscosity crude oil, and the adsorption rate was 10.83 g / (g·min).

[0103] Example 5:

[0104] (1) Formulation of GO-O / W emulsion

[0105] Cyclohexane and graphene oxide aqueous dispersion were mixed at a volume ratio of 1:1.25 and subjected to high-speed shearing to prepare an unstable GO-O / W emulsion.

[0106] (2) Preparation of graphene oxide solid hydrogel

[0107] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 hour to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 hour to obtain graphene solid hydrogel.

[0108] (3) Preparation of graphene oxide aerogel

[0109] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water inside and on the surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0110] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400℃ for 2 hours to obtain a graphene aerogel with multiple channels, such as... Figure 2 As shown.

[0111] (5) Thermal conductivity measurement

[0112] The thermal conductivity of the graphene aerogel with multiple channels prepared by (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.115 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.076 W / (m·K).

[0113] (6) Photothermal adsorption of crude oil

[0114] Under light irradiation, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. Figure 3 The figure shows the mass change of adsorbed high-viscosity oil over time. When adsorption reaches saturation, each gram of aerogel can adsorb 248.09 times its own mass of high-viscosity crude oil, with an adsorption rate of 10.79 g / (g·min). Figure 4 As shown, during this process, the temperature of the upper surface of the sample first increases and then decreases, while the temperature of the lower surface continues to increase.

[0115] Example 6:

[0116] (1) Formulation of GO-O / W emulsion

[0117] Cyclohexane and graphene oxide aqueous dispersion were mixed at a volume ratio of 1:1.25 and subjected to high-speed shearing to prepare an unstable GO-O / W emulsion.

[0118] (2) Preparation of graphene oxide solid hydrogel

[0119] The GO-O / W emulsion obtained in (1) was frozen at 1°C for 1 hour to solidify the cyclohexane droplets inside, and then placed on a cold source at -25°C for unidirectional freezing for 1 hour to obtain graphene solid hydrogel.

[0120] (3) Preparation of graphene oxide aerogel

[0121] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water inside and on the surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores.

[0122] (4) The graphene oxide aerogel obtained in step (3) is reduced at 700°C for 2 hours to obtain a graphene aerogel with multiple channels.

[0123] (5) Thermal conductivity measurement

[0124] The thermal conductivity of the graphene aerogel with multiple channels prepared in (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.095 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.074 W / (m·K).

[0125] (6) Photothermal adsorption of crude oil

[0126] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. When the adsorption reached saturation, each gram of aerogel could adsorb 229.83 times its own mass of high-viscosity crude oil, and the adsorption rate was 11.21 g / (g·min).

[0127] Example 7:

[0128] (1) Formulation of GO-O / W emulsion

[0129] An unstable GO-O / W emulsion was prepared by mixing n-dodecane and graphene oxide aqueous dispersion at a volume ratio of 1:1.25 and then subjecting the mixture to high-speed shearing.

[0130] (2) Preparation of graphene oxide solid hydrogel

[0131] The GO-O / W emulsion obtained in (1) was subjected to unidirectional freezing at -5°C for 1 hour to solidify the aqueous phase. Then it was placed at -25°C for 1 hour to completely solidify the n-dodecane droplets, thus obtaining a graphene solid hydrogel.

[0132] (3) Preparation of graphene oxide aerogel

[0133] The graphene oxide solid hydrogel obtained in step (2) was vacuum dried at 3 Pa for 24 h to remove water from the inside and surface of the pores, thus obtaining a graphene oxide aerogel with multiple pores, such as... Figure 5 As shown.

[0134] (4) The graphene oxide aerogel obtained in step (3) is reduced at 400°C for 2 hours to obtain a graphene aerogel with multiple channels.

[0135] (5) Thermal conductivity measurement

[0136] The thermal conductivity of the graphene aerogel with multiple channels prepared by (4) was measured using a laser thermal conductivity meter. The thermal conductivity along the ice crystal growth direction was 0.107 W / (m·K), and the thermal conductivity perpendicular to the ice crystal growth direction was 0.082 W / (m·K).

[0137] (6) Photothermal adsorption of crude oil

[0138] Under light, the graphene aerogel with multiple channels obtained in (4) was placed on the surface of crude oil (viscosity of 25574.1 mPa·s at 25℃) along the ice crystal growth direction. When the adsorption reached saturation, each gram of aerogel could adsorb 264.31 times its own mass of high-viscosity crude oil, and the adsorption rate was 9.25 g / (g·min).

[0139] Compared with the prior art, the beneficial effects of the present invention include at least the following:

[0140] (1) The preparation method of the graphene aerogel described in this invention is simple, low in cost, and can be prepared on a large scale, with broad application prospects.

[0141] (2) The preparation method adopted in this invention is to shape the material into isotropic primary channels by unstable GO-O / W emulsion droplets; then, one phase is solidified by step-cooling unidirectional freezing, and then another phase is solidified, thereby stabilizing the primary channels and promoting the directional arrangement of the primary channels to form the final multi-channel structure. Step-cooling unidirectional freezing can make the multi-channel graphene aerogel have an anisotropic structure. By simply adjusting the freezing temperature and the volume ratio of the oil phase to the water phase, materials with different properties can be prepared.

[0142] (3) The graphene aerogel with multiple channels described in this invention has high porosity, anisotropic thermal conductivity, good thermal insulation performance perpendicular to the channel arrangement direction, good heat transfer performance parallel to the channel arrangement direction, high adsorption rate and large adsorption amount for crude oil, and can be used as both thermal insulation material and adsorption material at the same time. It can be widely used in energy conservation, environmental protection and other fields.

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the claims of the present invention.

Claims

1. A method for preparing graphene aerogel with multiple channels, characterized in that, Includes the following steps: An unstable oil-in-water emulsion is obtained by mixing an aqueous dispersion of graphene oxide with an oil phase at a set volume ratio and then shearing it at high speed. The oil phase consists of substances that are incompatible with water and have different freezing points under the same pressure. The set volume ratio of the oil phase to the water phase is 1:1 to 1:

5. The obtained oil-in-water emulsion is subjected to stepwise unidirectional freezing to obtain graphene oxide solid hydrogel through stepwise solidification of water and oil. The stepwise unidirectional freezing specifically includes: placing the obtained oil-in-water emulsion in a mold, so that its bottom surface contacts an ultra-low temperature cold source, and performing unidirectional freezing; during the unidirectional freezing process, the mold containing the oil-in-water emulsion is placed at a temperature below the solidification point of one phase and above the solidification point of the other phase for a set time, and then placed at a temperature below the solidification point of the other phase for a set time. The obtained graphene oxide solid hydrogel was vacuum dried to remove oil and water from the inside and surface of the pores, thus obtaining graphene oxide aerogel with multiple pores. The obtained graphene oxide aerogel was reduced at high temperature to obtain a graphene aerogel with multiple pores.

2. The method for preparing a graphene aerogel with multiple channels according to claim 1, characterized in that, The high-speed shearing rotation speed is not less than 10,000 r / min, and the time is 1 to 5 min.

3. The method for preparing a graphene aerogel with multiple channels according to claim 1, characterized in that, The mold is made by wrapping the top and sides of the aerogel container with heat insulation material, leaving only the bottom of the container unwrapped, so that the bottom is in contact with the ultra-low temperature cold source.

4. The method for preparing a graphene aerogel with multiple channels according to claim 3, characterized in that, The ultra-low temperature cold source can be any one of a refrigerant or a refrigeration device.

5. The method for preparing a graphene aerogel with multiple channels according to claim 1, characterized in that, The vacuum drying pressure is 10 Pa or less, and the time is 12 hours or more; The high-temperature reduction temperature is 200~700℃.

6. An application of a graphene aerogel prepared by the preparation method according to any one of claims 1-5, characterized in that, The method of applying graphene aerogel with multiple channels to thermal insulation involves attaching the internal channels of the graphene aerogel material parallel to the surface of the object requiring thermal insulation, thereby blocking heat transfer.

7. An application of a graphene aerogel prepared by the preparation method according to any one of claims 1-5, characterized in that, The graphene aerogel with multiple pores is used in a photothermal oil absorption method. Under sunlight, the graphene aerogel material with its internal pores perpendicular to the oil surface is placed on the oil surface. After absorbing light, the material heats up and heats the oil, reducing the oil viscosity and achieving adsorption.

Citation Information

Patent Citations

  • Preparing method of aperture-adjustable graphene aerogel

    CN109133040A

  • Graphene composite aerogel preparation method

    CN107732215A

  • All-carbon graphene aerogel and preparation method thereof

    CN110562964A